Development of automated visual tracking system for surgical instruments / Nur Athirah Yazid - Nur Athirah, Yazid (2016)
Surgical instrument processing is crucial for safety, high-quality surgical care but has received a little thought in the medical literature. Typical hospitals have inventories in the tens of thousands of surgical instruments organized into thousands of instrument sets. The use of these instruments for many procedures per day leads to millions of instrument sets being reprocessed yearly in a single hospital (Blackmore, Bishop, Luker, & Williams, 2013). In this project student are proposing a potential method to provide solution to the problem of errors in the processing of sterile instruments that lead to increased functioning times and costs. Automated Visual Tracking System comprised of a system on which the names and pictures of surgical instruments required for a surgical procedure are selectively displayed for reading the optically readable code mark; and a computer which stores the data about surgical instruments for the surgical procedure. The optically readable code mark on a surgical instrument is read by the reader and inputted into the computer, by which the read and inputted surgical instruments are consecutively identified on a screen, and finally the preparation of surgical instrument sets can be prepared. Development of Visual Tracking System for Surgical Instrument is to help to minimize problems that may arise in tracking instruments and to make the management become more efficient. Detection system equipment can then be used to set up a database of information about where each piece of equipment is in the right location. In particular, readers are actively or passively can provide information concerning the completeness of whether the detection system center or remotely via the electrical wiring of the existing or via a network or other system that can carry any information (Black, 1999) using a bar code requires labor -intensive steps to visit the facility with one or more mobile scanner.